Arctic Rain on Snow Dataset, 1931 - 2023 ... - Barrett, Andrew (NSF Arctic Data Center, 2024)
Rain on snow events occur when liquid precipitation falls on snow cover and refreezes. Ice crusts that form within the snow pack can have severe consequences for wildlife, infrastructure, and communities. Every rain on snow (ROS) event has its own character — no two are alike. Differences range in affected area size, duration, severity, and lasting effects. What is still unknown is to what degree ROS events as a whole will change, in frequency and intensity, in the coming years. The Arctic Rain on Snow database will help to start answering questions about the frequency and character of past and present rain on snow events, and aid in determing conditions and predictions for future events. Station records for 244 Automatic Surface Observing Systems (ASOS) stations across the Arctic were downloaded from the Iowa State University Iowa Environmental Mesonet site. Records include 2 m air and dew point temperatures, and present weather codes. Weather codes describe current weather condition and precipitation type, ...